Upaya Penatalaksanaan Pola Nafas Tidak Efektif pada Pasien Congestive Heart Failure - Sitta Nurlaela, Erika, Ns. Arief W. Jadmiko, S.Kep., M.Kep (2017)
Congestive heart failure is a disorder of cardiac function failure in pumping blood to the needs tubuh.Penyakit cells can cause death for the sufferer, the incidence of heart failure in Indonesia has increased from year to year that often arise.Gejala because heart failure are dyspnea or shortness of breath, it happened because of a buildup of fluid in lung tissue.As a result the patients breathing pattern becomes ineffective. Describe the management efforts ineffective breathing pattern in patients with heart failure.The descriptive method with case study approach in the HCU. The collection of data by observation, physical examination, medical records, interviews, documentary studies of journals and books.Patients showed improvement after the act of breathing patterns. There is the influence of exercise oxygenation therapy, bed rest and the ideal semi-Fowler's position.The problem in patients with Ineffective breathing pattern is not resolved because nursing care for patients does not increase the effectiveness of breathing patterns in accordance with the criteria that have the desired result. The act of deep oxygenation therapy, bed rest and the ideal semi-Fowler's position can be performed as an input in independent nursing actions to handle Ineffective breathing pattern, as is maximal in improving the patient's breathing pattern.